Effects of natural and anthropogenic storm-stranded debris in upper-beach arthropods: Is wrack a prey hotspot for birds? - Laurino, Ivan Rodrigo Abrão; Lima, Tamiris Pereira [UNESP]; Turra, Alexander (Elsevier, 2023)
Storm-stranded debris (i.e., wrack) are important components for the functioning of beach ecosystems. With the current increase in extreme storm events, beached wrack is expected to change globally. However, little is known about how different types of wrack can affect beach biodiversity. Here, we hypothesized that natural debris (algae and land–plant debris) would optimize the short-term aggregation of benthic arthropods on the beach ecosystem, while anthropogenic debris (plastics) would not perform this function. We also expected that short-term aggregations of arthropods in the natural debris would create a transient prey hotspot (i.e., points of high prey concentration) for birds on the beach. Thus, we performed manipulative field experiments with debris addition and predator exclusion by cage on a short temporal scale (maximum 20 days). We found that natural debris aggregated higher community abundances than anthropic debris and treatments without debris, while community richness was not affected by wrack. No differences were noted when comparing the community aggregation on plastic debris and treatments without debris. The coleopterans were the group responsible for this aggregation, mainly represented by Phaleria testacea, which aggregated on natural debris with abundances five times greater than those on plastic debris. Nevertheless, we did not find any evidence of increased predation by birds on the coleopterans aggregated in the natural debris. We conclude that arthropod aggregation in the wrack is a phenomenon primarily associated with natural debris, not occurring in plastic debris, although the role of this faunal aggregation as a prey hotspot for birds was not evident in the short term. These results showed that the wrack type matters in terms of consequences for beach arthropods, creating concerns against beach cleaning methods that are adopted indiscriminately, also signaling the need for long-term studies to proceed with investigating the wrack functions for top predators on sandy beaches.
Keywords: Algae debris; Benthic macrofauna; Land–plant debris; Phaleria testacea; Plastic pollution; Predator exclusion